Analisis Faktor yang Berhubungan Dengan Pemilihan KB Suntik di Puskesmas Tinggi Hari Kabupaten Lahat Tahun 2021 - Yemi Eliarti (Fakultas Ilmu Kesehatan Universitas Katolik Musi Charitas, 2022)
Planned contraception with the injection method is widely used by couples of childbearing age, because it is more practical. Easy to obtain in health services compared to other methods.This study aims to determine the factors associated with the use of injectable family planning at the Tinggi Hari Health Center, Gumay Ulu subdistrict,Distrct Lahat in 2021. The design of this study used a cross sectional, where the population in this study were women of childbearing age in the work area of ??the Puskesmas Tinggi days in 2021. The method of sampling in this study was the purposive sampling technique. The sampling method of this research was determined by purposive sampling. The research sample is women of childbearing age who make family planning visits in 2021 in the Work area of ??the Hari Tinggi Health Center, Gumay Ulu subdistrict,Distrct Lahat is 92 people. This research has been carried out in June-July 2021. Data collection using questionnaires. The results of statistical test analysis using the Chi-Square statistical test where the results show there is a significant relationship (p < 0.05) for the variable availability of facilities (p value 0.02) and husband's support (p value 0.01). There is no relationship between age (p value 0.21) and education variable (p value 0.08). From the results of the multivariate statistical test, the dominant factor was obtained, namely the husband's support variable (p value 0.006) with an OR value (0.285).